“Roasting” Dalam Perspektif Etika Komunikasi Islam Fajri Chairawati - Fajri Chairawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Roasting is a form of communication that involves ridiculing, ridiculing, or humorously making fun of someone or something with the aim of entertaining or producing a funny reaction. In the context of roasting, participants use sharp expressions, sarcasm, or excessive comparisons to make the interlocutor or target laugh. Roasting is often done with the aim of entertaining and strengthening social bonds, but it can also have the potential to hurt other people's feelings if it is not done wisely or crosses appropriate boundaries. This is what the author wants to study regarding roasting when viewed from the perspective of Islamic communication ethics. The method used is descriptive qualitative research type with library research. Data was obtained from books, journals, articles related to roasting and Islamic communication ethics. From the studies that have been carried out, the results show that from the perspective of Islamic communication ethics, roasting is not recommended. Islam teaches mutual respect and respect for each other, including in communicating between individuals, which includes communication ethics using good and polite language and speech.